1998
DOI: 10.1093/oxfordjournals.aje.a009633
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cotinine Concentration and Self-reported Smoking during Pregnancy

Abstract: Although during pregnancy there is a better correlation between maternal serum cotinine concentration and adverse outcome than between self-reported smoking and such an outcome, few studies of pregnancy have measured cotinine concentration to determine how much a woman smokes. This study assessed the accuracy of self-reported smoking during pregnancy by performing serum cotinine assays on 448 women registered in the Collaborative Perinatal Project (1959-1966). Based on the assumption that a serum cotinine conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
159
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(174 citation statements)
references
References 14 publications
12
159
1
2
Order By: Relevance
“…In previous studies that examined the accuracy of self-reported behaviors with drug test results among pregnant women, most have found fairly good agreement on usage with slight under-reporting of amount of alcohol consumption (10,11) or number of cigarettes smoked (23,24). In our study, we did not perform laboratory tests measuring drug levels for cigarette smoking or alcohol use and therefore could not assess validity.…”
Section: Discussionmentioning
confidence: 72%
“…In previous studies that examined the accuracy of self-reported behaviors with drug test results among pregnant women, most have found fairly good agreement on usage with slight under-reporting of amount of alcohol consumption (10,11) or number of cigarettes smoked (23,24). In our study, we did not perform laboratory tests measuring drug levels for cigarette smoking or alcohol use and therefore could not assess validity.…”
Section: Discussionmentioning
confidence: 72%
“…Among pregnant smokers, maternal levels of cotinine correlate better with outcome measures such as birth weight than the number of cigarettes smoked per day (Haddow et al, 1987;Mathai et al, 1990;Bardy et al, 1993;Li et al, 1993;Ellard et al, 1996;Klebanoff et al, 1998;SeckerWalker et al, 1998). Recently, a study of women during pregnancy and again postpartum found that during pregnancy the median saliva cotinine concentration per cigarette was 3.5 ng/ml versus 9.9 ng/ml when not pregnant (Rebagliato et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 448 women using a maternal serum cotinine concentration of >10.0 ng/mL to define tobacco users determined that 94.9% of women who denied smoking and 87.0% of women who stated they smoked reported their status accurately (kappa=0.83). 14 Kvalvik et al studied a subsample of 2,997 women in the Norwegian Mother and Child Cohort Study (MoBa) to assess selfreported tobacco use and plasma cotinine concentrations at 18 weeks gestational age using a cutoff of 12ng/mL. 15 The sensitivity and specificity for self-reported smoking was 82% and 99% respectively.…”
Section: Discussionmentioning
confidence: 99%